Minimum Wages and Employment: The Case of German Unification - Bernhard Heitger (Kiel Institute of World Economics (IfW), 2001)
Analysis in terms of the two-sector open economy shows that in bringing the market economy to East Germany, West Germany seems to have disregarded important fundamentals. Premature formation of a currency union led to a substantial real appreciation of the East German currency. Premature implementation of the West German system of wage bargaining resulted in inappropriate minimum wage schedules. Both measures made East German production possibilities and employment decline.
Keywords: P23; E24; 330; Minimum Wages; Employment; German Unification; Lohnniveau; Mindestlohn; Kleines-offenes-Land; Handelbares Gut; Nicht-handelbares Gut; Lohnverhandlungen; Beschäftigungseffekt; Schätzung; Neue Bundesländer